Keeping the faith: early Christian intaglios as indexes of agency. - Faux, Hannah (Archaeology International, 2024)
This article is based on observations taken from my 2019 MA research, which assessed how the selection and treatment of iconography on early Christian Roman intaglio gemstones affected their agency. It established the range of themes and motifs available to early Christian artists by analysing records of more than 1,000 early Christian sarcophagi from the Index of Medieval Art, comparing rates of iconographic and thematic occurrence with a dataset of more than 400 early Christian intaglios. This established the range of themes and motifs that were available to artists. By using sarcophagi as a proxy, it was possible to observe patterns of selection on the gemstones. This enabled an assessment of the significance of selections and combinations and an evaluation of their treatment through iconographical analysis. Applying the concept of material agency to gemstones offers an insight into how choices affected their function, enabling an exploration of the relationships between the objects, their compositional elements and their viewers. This provided another insight into certain iconographic choices and how these may have shaped how the gems acted on their owners. The sarcophagi and the gemstones depict a similar range of themes; however, the sarcophagi corpus features an expanded repertoire of New Testament images, whereas the gemstones exhibit a range of 'magical' components combined in a manner that is unique to the gems. The designs on both types of object use sophisticated compositional techniques that initiate engagement in their viewers; however, the gemstone's miniature, portable nature enables them to mediate agency in a way that is specific to the gems.